Ergodicity of nonlinear transformations - Ganikhodjaev, Nasir (Eudoxus Press, LLC, 2009)
We study the asymptotic behavior of nonlinear dynamical system,that has biological significance.Then otion of regular direct product of two quadratic stochastic operators is introduced.